International society of sports nutrition position stand: coffee and sports performance - Lowery, L. M.; Anderson, D. E.; Scanlon, K. F.; Stack, A.; Escalante, G.; Campbell, S. C.; Kerksick, C. M.; Nelson, M. T.; Ziegenfuss, T. N.; van Dusseldorp, T. A.; Kalman, D. S.; Campbell, B. I.; et al. (Journal of the International Society of Sports Nutrition, 2023)
Based on review and critical analysis of the literature regarding the contents and physiological effects of coffee related to physical and cognitive performance conducted by experts in the field and selected members of the International Society of Sports Nutrition (ISSN), the following conclusions represent the official Position of the Society: